Steering the Ship through Uncertain Waters: Empirical Analysis and the Future of Evangelical Higher Education. Issue 1 (1st January 2016) - Rine, P. Jesse; Guthrie, David S.
ABSTRACT: Leaders of evangelical Christian colleges must navigate a challenging environment shaped by public concern about college costs and educational quality, federal inclinations toward increased regulation, and lingering fallout from the Great Recession. Proceeding from the premise that empirical analysis empowers institutional actors to lead well in uncertain times, this article examines four key areas—access, affordability, student outcomes, and financial sustainability—using publicly available data from the Integrated Postsecondary Education Data System (IPEDS). Results for the evangelical segment and the wider private nondoctoral sector of American higher education are compared, and areas of relative strength and weakness are considered. To facilitate benchmarking by institutional research professionals, the article's appendix presents national longitudinal norms for both the evangelical segment and the private nondoctoral sector.